NTFP commercialisation in Zimbabwe - Braedt, O.; Campbell, Bruce M. (2001)
A study of the woodcraft sector in Zimbabwe was conducted to understand the potential role of NTFP commercialisation in rural households. Zimbabwe experienced an uosurge in the marketing of wodcarvings and other craft articles during the 1990s. Possible social and ecological impacts originating from this informal commerce have alarmed environmentalists, governmental and non-governmental intitutions, and policy makers. Up to the time of the study no clear policy on the woodcarving sector was apparent, with some institutions promoting it as means to improving income, while other intitutions were involved in trying to halt the sector, using the current legislation to guide their actions.